2003
DOI: 10.1128/jb.185.15.4626-4629.2003
|View full text |Cite
|
Sign up to set email alerts
|

Competition between MutY and Mismatch Repair at A · C Mispairs In Vivo

Abstract: We show that the MutY protein competes with the MutS-dependent mismatch repair system to process at least some A ⅐ C mispairs in vivo, converting them to G ⅐ C pairs. In the presence of an increased dCTP pool resulting from the loss of nucleotide diphosphate kinase, the frequency of A ⅐ T3G ⅐ C transitions at a hot spot in the rpoB gene is 30-fold lower in a MutY-deficient derivative than in the wild type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
2
33
2
Order By: Relevance
“…The results are reproducible and are statistically significant (P ϭ 0.008). These results differ from the findings of Kim et al (27), who mentioned that the mutation frequencies of mutS and mutS mutY were similar. No data, however, were shown to support those findings of Kim et al (27).…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…The results are reproducible and are statistically significant (P ϭ 0.008). These results differ from the findings of Kim et al (27), who mentioned that the mutation frequencies of mutS and mutS mutY were similar. No data, however, were shown to support those findings of Kim et al (27).…”
Section: Resultscontrasting
confidence: 57%
“…E. coli chromosomal DNA was isolated using a genomic DNA purification kit (Gentra System, Minneapolis, MN). The main group of mutations (cluster II) of the rpoB gene was PCR amplified using Chang440 and Chang441 primers (see Table S1 in the supplemental material) as described previously (27). The PCR product was purified with the QIAquick PCR purification kit (QIAGEN, Valencia, CA) and sequenced directly with Chang442 primer.…”
Section: Methodsmentioning
confidence: 99%
“…Whether error correction by epsilon is biased has been debated for years, but a recent study (56) showed a bias toward correcting G:C > A:T mutations that would account for our results. Another candidate is MutY, which can remove an A mispaired with C, preventing G:C > A:T mutations if C is the template (and promoting A:T > G:C mutations if A is the template) (57). Future MA studies will reveal if these enzymes contribute to mutational specificity in the absence of MMR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Richardson et al (40,41) found that mutS and mutL deficiencies only partly explain the high mutation rate of some MC isolates. As MutY represents a mismatch excision function in removing adenine opposite guanine (32) or cytosine (51) and previously has been shown to overlap with E. coli MMR in vivo (22), a coupling between MC BER and MMR could result in a hypermutator phenotype of mutY mutant strains.…”
Section: Discussionmentioning
confidence: 99%